2021
DOI: 10.14806/ej.26.1.973
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Instagram Addiction Scale in Greek Youth

Abstract: Instagram is one of the fastest growing social networking platforms. A body of evidence suggests that Instagram problematic use and addiction have negative effects on the psychological well-being of young people. The Instagram Addiction Scale, a self-report tool assessing Instagram problematic use and addiction, has been developed recently. The aim of the present study was to validate the Instagram Addiction Scale in the Greek language and to assess its psychometric properties. An online and on-print self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The findings here are in line with those obtained in the original study (Kircaburun & Griffiths, 2018) and two other validation studies (i.e. Greek [Zarenti et al, 2021] and Persian [Sharifi Fard et al, 2021] versions) demonstrating: (i) the stability and coherence of the IAS-15 (ii) the replication of the scale's factorial structure, (iii) items with high and significant factor loadings, and (iv) the adequate indices of fit between the data and the proposed model (as demonstrated in the CFA). This makes the Italian IAS-15 a valuable tool for assessing the severity of Instagram addiction among Italian adults, especially in the context of epidemiological research.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings here are in line with those obtained in the original study (Kircaburun & Griffiths, 2018) and two other validation studies (i.e. Greek [Zarenti et al, 2021] and Persian [Sharifi Fard et al, 2021] versions) demonstrating: (i) the stability and coherence of the IAS-15 (ii) the replication of the scale's factorial structure, (iii) items with high and significant factor loadings, and (iv) the adequate indices of fit between the data and the proposed model (as demonstrated in the CFA). This makes the Italian IAS-15 a valuable tool for assessing the severity of Instagram addiction among Italian adults, especially in the context of epidemiological research.…”
Section: Discussionsupporting
confidence: 92%
“…The analysis of the Italian IAS-15 reliability and validity coefficients showed good and consistent psychometric properties. More specifically, comparing the goodness of fit indices (GOFs) with the other validation studies (i.e., Greek [Zarenti et al, 2021] and Persian [Sharifi Fard et al, 2021] versions), the present study found similar or better values (i.e., RMSEA, GFI). These results demonstrate that the Italian IAS-15 is very robust from a factorial structure point of view and the factor loadings of the items were all significant and high.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Various tools have been developed to assess Instagram addiction and its various aspects, including the 15-item Instagram Addiction Scale (IAS-15; , the 20-item Instagram Addiction Scale (IAS-20; Sholeh & Rusdi, 2019, and the 34-item Instagram Addiction Test (IAT;Souza, Sami Yukta & Be Vera, 2018). Validation and reporting of IAS psychometric properties has also been carried out in several countries (Zarenti et al, 2021;Pekpazar, Aydin, Aydin, Beyhan & Ari, 2021). Therefore, the present study evaluated the psychometric properties of the IAS-15 among Iranian students.…”
Section: Introductionmentioning
confidence: 99%